THE CONSUMPTION EFFECT OF HOUSEHOLD DEBT: EVIDENCE FROM INDONESIA - Pihri Buhaerah (Economic Research Center, the Indonesian Institute of Sciences (P2E-LIPI), 2022)
This paper empirically examines the relationship between household debt and household consumption growth in Indonesia using the ARDL model. This paper employs quarterly time series data on Indonesian household consumption expenditures and household debt from 2002 to 2017. The results of regression analysis showed negative relationships between household debt and consumption growth in the long run, while positive linkage was found in the short run. Specifically, in the long run, a 10 percentage points increase in household debt was associated with decreasing household consumption growth by 6 percent. In contrast, in the short-run, a 10 percent increase in household debt was associated with increasing consumption growth by 29 percentage points. Thus, although the effect of household debt on consumption growth is positive in the short term, it is negative in the long term. Interestingly, the positive effect is seen to decrease when the ratio of household debt to GDP is above 12.2 percent.